Buried in the red dirt : race, reproduction, and death in modern Palestine - Hasso, Frances Susan (Cambridge University Press, 2022)
Bringing together a vivid array of analog and non-traditional sources, including colonial archives, newspaper reports, literature, oral histories, and interviews, Buried in the Red Dirt tells a story of life, death, reproduction and missing bodies and experiences during and since the British colonial period in Palestine. Using transnational feminist reading practices of existing and new archives, the book moves beyond authorized frames of collective pain and heroism. Looking at their day-to-day lives, where Palestinians suffered most from poverty, illness, and high rates of infant and child mortality, Frances Hasso's book shows how ideologically and practically, racism and eugenics shaped British colonialism and Zionist settler-colonialism in Palestine in different ways, especially informing health policies. She examines Palestinian anti-reproductive desires and practices, before and after 1948, critically engaging with demographic scholarship that has seen Zionist commitments to Jewish reproduction projected onto Palestinians. This title is also available as Open Access on Cambridge Core.